Karakteristik dan Studi Kasus Penerimaan Mi Sagu oleh Masyarakat di Sulawesi Selatan (Characteristics and Case Study of Sago Noodle's Acceptability by Consumer in South Sulawesi) - Endang Y. Purwani; Y. Setiawaty; H. Setianto; Widaningrum Widaningrum (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
Noodle is the most popular product for the Indonesian people. It could be served conveniently without inferior image. Development of transparent noodle would promote consumption of saga Therefore, sago image as staple food would increase as superior as rice grain or wheat. The objectives of the research were to evaluate transparent noodle quality made from two types of sago starches and their acceptability by consumer (case: South Sulawesi). Noodle was prepared by mixing the thy sago starch with